2015
DOI: 10.1515/jengeo-2015-0009
|View full text |Cite
|
Sign up to set email alerts
|

Factors Responsible For Rural Residential Water Supply Shortage In Southeastern Nigeria

Abstract: Efficient water supply is very crucial to sustenance of socio-economic growth, poverty attenuation, and food security. In most rural areas of developing countries including Nigeria water supplies are not commensurate with demand leading to a shortfall in water use and many people suffer from this scenario. This research investigated the factors responsible for rural residential water supply shortage in Southeastern Nigeria. Data were collected through the use of four mixed but complimentary methods namely ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…It also reflects the general geography of water availability in Africa with a tendency to have water scarcity increase with the distance away from the equator especially to the north. Studies by Fagoyinbo (2015) and Obeta & Nwankwo (2015) opined that the variation in the water yield of the aquifers is a function of geologic characteristics and the interplay between rock fractures in the aquifer -which provide storage and recharge to the bedrock. As such, the correlation analyses of the households' water supply dynamics and the study zones, computed using SPSS, revealed that the Chad Formation has insignificant relationships, while Kerri-Kerri Formation and Fika Shale have significant associations at certain levels.…”
Section: Discussion Of the Study Findingsmentioning
confidence: 99%
“…It also reflects the general geography of water availability in Africa with a tendency to have water scarcity increase with the distance away from the equator especially to the north. Studies by Fagoyinbo (2015) and Obeta & Nwankwo (2015) opined that the variation in the water yield of the aquifers is a function of geologic characteristics and the interplay between rock fractures in the aquifer -which provide storage and recharge to the bedrock. As such, the correlation analyses of the households' water supply dynamics and the study zones, computed using SPSS, revealed that the Chad Formation has insignificant relationships, while Kerri-Kerri Formation and Fika Shale have significant associations at certain levels.…”
Section: Discussion Of the Study Findingsmentioning
confidence: 99%
“…Cleaning, constructing tank and fencing at the water source were some of the water source management adopted by the residents. [12] based on analysis of the factors responsible for water supply shortage in the study area, they recommended that conserving water to reduce water waste is a first step in water management, thus the communities should adopt various water conservation measures such as installing concrete tanks in springs to avoid the waste of the spring water and to protect it from contamination. Households should install large tank particularly underground tanks for collection of rain water in the wet season which can be used when springs and streams yield small quantity of water in the dry.…”
Section: Water Source Managementmentioning
confidence: 99%
“…Figure 1. Location of the study area (Source: modified from Obeta and Nwankwo, 2015) 2. Materials and Methods…”
Section: Contributing Factormentioning
confidence: 99%